Flexible and broadly tunable infrared light source based on shaped sub-10-fs pulses for a multimodal microscopy setup - Brückner, Lukas; Müller, Niklas; Motzkus, Marcus (Optics letters, 2018)
We present a versatile approach for mid-infrared spectroscopy through the flexible control of a difference-frequency-generation (DFG) process by femtosecond (fs) pulse shaping and spectral focusing. Based on a broadband sub-10-fs oscillator, the spectral position and spectral resolution can be independently selected within the molecular fingerprint region of more than 2000  cm−1. A spectral resolution better than 20  cm−1 can be achieved, which depends solely on the pulse shaper configuration. An absorption experiment on a polystyrene reference sample finally validates the concept and opens the door for an additional modality in nonlinear multimodal microscopy setups.